Pengaruh Pengadaan Sumber Daya Manusia, Kompetensi Sumber Daya Manusia dan Dukungan Organisasi Terhadap Peningkatan Kinerja Organisasi Di PT Pupuk Indonesia Logistik - Agung Iman Santoso; Rakhmat; Asrul (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
The company PT Pupuk Indonesia Logistik (PILOG) is facing a decline in organizational performance, there are several factors that can be the cause. One of them is the lack of procurement and development of quality human resources (HR). High quality human resources are very important in achieving company goals and improving organizational performance. In this study it is doubted, how much influence pawnshops, competence and organizational support have on improving organizational performance at PT Pupuk Indonesia Logistik Jakarta. The results of the study show that partially or simultaneously there is a significant influence between HR procurement, HR competence and organizational support on organizational performance improvement variables.